A “new” economic elite in India: transnational and neoliberal? - Schöttli, Jivanta; Pohlmann, Markus (South Asia multidisciplinary academic journal, 2017)
Much of the globalization literature and accompanying theory project that, as countries integrate into the global economy, they will converge towards a transnational and neoliberal version of capitalism. It is presumed that this happens with the rise of international companies, which along with a transnational class of managers, enable the spread of neoliberal management thinking. In the wake of liberalization policies and reforms as well as the globalization and growth of India’s economy, and using life course data for more than one hundred Indian top managers, including information on nationality, time spent working and studying abroad, education background, career and mobility patterns, we explore the evidence for the emergence of a transnational and neo-liberal business elite in India. In the Indian case, we find that top managers are not composed of “transnational rootless company hoppers” but are dominated by “nationally recruited company men.”